Clinical findings just after return to play predict hamstring re-injury, but baseline MRI findings do not. Issue 18 (18th July 2014) - De Vos, Robert-Jan; Reurink, Gustaaf; Goudswaard, Gert-Jan; Moen, Maarten H; Weir, Adam; Tol, Johannes L
Abstract : Background: Acute hamstring re-injuries are common and hard to predict. The aim of this study was to investigate the association between clinical and imaging findings and the occurrence of hamstring re-injuries. Methods: We obtained baseline data (clinical and MRI findings) of athletes who sustained an acute hamstring injury within 5 days of initial injury. We also collected data of standardised clinical tests within 7 days after return to play (RTP). The number of re-injuries was recorded within 12 months. We analysed the association between the possible predictive variables and re-injuries with a multivariate Cox proportional-hazards regression model. Results: Eighty patients were included at baseline and 64 patients could be included in the final analysis because data after RTP were not available in 16 cases. There were 17 re-injuries (27%). None of the baseline MRI findings were univariately associated with re-injury. A higher number of previous hamstring injuries (adjusted OR (AOR) 1.33; 95% CI 1.11 to 1.61), more degrees of active knee extension deficit after RTP (AOR 1.13; 95% CI 1.03 to 1.25), isometric knee flexion force deficit at 15° after RTP (AOR 1.04; 95% CI 1.01 to 1.07) and presence of localised discomfort on hamstring palpation after RTP (AOR 3.95; 95% CI 1.38 to 11.37) were significant independent predictors of re-injury. Athletes with localised discomfort on hamstring palpation just after RTP were consequently almost four times more likely to sustain a re-injury. Conclusions: The number of previous hamstring injuries, active knee extension deficit, isometric knee flexion force deficit at 15° and presence of localised discomfort on palpation just after RTP are associated with a higher hamstring re-injury rate. None of the baseline MRI parameters was a predictor of hamstring re-injury. Trial registration number: ClinicalTrial.gov number NCT01812564 .